A flexible, robust cellulose/phytic acid/polyaniline hydrogel for all-in-one supercapacitors and strain sensors. Issue 33 (12th August 2022) - Wan, Huixiong; Qin, Chaoran; Lu, Ang
Abstract : An easy handing method was designed to prepare a cellulose-based conductive hydrogel for high performance all-in-one supercapacitors and highly sensitive strain sensors. Abstract : Herein, a flexible, stretchable and highly ionic conductive cellulose/phytic acid/polyaniline hydrogel with sandwich-shaped structures was fabricated by in situ growth of polyaniline onto a cellulose/phytic acid hydrogel. The as-prepared conductive hydrogel was assembled into an all-in-one supercapacitor. Benefiting from the in situ polymerized polyaniline particles in the cellulose matrix, which effectively reduced the interfacial resistance between the electrode and electrolyte, the all-in-one supercapacitor showed a high areal capacitance of 1210.7 mF cm −2 at a current density of 1 mA cm −2, a maximum energy density of 168.2 μW h cm −2 and a maximum power density of 669.1 μW cm −2, outperforming reported flexible all-in-one supercapacitors. The capacitance also remained at 89% after 1000 bending cycles, due to the excellent mechanical properties. On the other hand, the cellulose/phytic acid/polyaniline hydrogel also demonstrated great potential as a strain sensor due to the enhanced conductivity caused by involving polyaniline. A zig-zag pattern was introduced to realize strain-controlled contact of resistive hydrogel traces, and the structural strain sensor demonstrated a high gauge factor up to 20.74, capable of detecting most human activities with high sensitivity and durability. The present work shed light on the design and fabrication of cellulose hydrogel-based electronic devices with high performance for real-life scenarios.